×

Hello! Socratic's Terms of Service and Privacy Policy have been updated, which will be automatically effective on October 6, 2018. Please contact hello@socratic.com with any questions.

How do you prove #cos 3 theta = 4 cos^3 theta - 3 cos theta#?

1 Answer
Jun 6, 2016

Answer:

Proof is given below.

Explanation:

#cos3theta=cos(2theta+theta)#

#=cos2thetacostheta-sin2thetasintheta#

#=(cos^2theta-sin^2theta)costheta-2sinthetacosthetasintheta#

#=cos^3theta-sin^2costheta-2sin^2thetacostheta#

#=costheta(cos^2theta-sin^2theta-2sin^2theta)#

#=costheta(cos^2theta-3sin^2theta)#

#=cos^3theta-3sin^2thetacostheta#

#=cos^3theta-3(1-cos^2theta)costheta#

#=cos^3theta-3costheta+3cos^3theta#

#=4cos^3theta-3costheta#